PENGARUH GAYA HIDUP DAN KELAS SOSIAL TERHADAP KEPUTUSAN BERKUNJUNG PADA CAFÉ SUNSHINE KOTA BIMA - Ita Purnama, M.Pd., MM. Inov; M Sebrio; Nur Khusnul Hamidah., SE, MM (Universitas Mahendradatta, 2025)
This research aims to determine lifestyle and social class on the decision to visitCafé Sunshine, Bima City. This type of research is associative to determine the causalrelationship between two or more variables. The population used in this research is in thecity of Bima with an unknown population where the sample used is 55 with a purposivesampling technique. Data collection techniques are through observation, questionnaires,literature study using data analysis techniques, validity test, reliability test, classicalassumption test, multiple linear regression test, determination and correlation, t test and ftest. The results of research carried out by researchers are 1.) the influence of lifestyle (X1)has a significant effect with a t-count value of 3,579 > t-table of 2,007 with a significancevalue of 0.001 < 0.05 2.) the influence of social class (X2) has an influence significantly witha t-count value of 3,439 > t-table of 2,007 with a significance value of 0.001 < 0.05 3.)lifestyle and social class simultaneously influence the decision to visit the Sunshine Café inBima City with an f-count of 23,273 > f -table of 3.18 with a significance of 0.000 <0.05, it isconcluded that the third hypothesis states that